Sustainable Resin Tapping in Nepal: Challenges and Opportunities (A case from Salyan District) - Paudyal, Dhananjaya (The Initiation, 2010)
This paper attempts to explore a case from Salyan district on resin tapping and its contribution to local and national economy. Resin tapping and its related activities like extraction, collection and transportation are one of the major sources of employment for a large number of rural poor people. Based on the quantity of resin collected and exported outside the district, revenue is generated to central as well as local government and Community Forest User Groups (CFUGs). In the mean time, some issues and challenges have been identified at local level regarding the sustainability of resin tapping. It, therefore, concludes that some practical measures are necessary to overcome the issues and challenges so that resin tapping could be done in a sustainable manner. Sources of information of this paper are records of District Forest Office and rosin companies and net surfing as secondary sources; field observation, interviews with CFUGs and resin collectors as primary sources. Key Words: Pine forests, Resin tapping, Sustainability, Revenue, Employment, Nepal DOI: 10.3126/init.v2i1.2540 The Initiation Vol.2(1) 2008 pp172-179